Behavioural interventions for HIV positive prevention in developing countries: a systematic review and meta-analysis - Caitlin E Kennedy; Amy M Medley; Michael D Sweat; Kevin R O'Reilly (The World Health Organization, 2010)
OBJECTIVE: To assess the evidence for a differential effect of positive prevention interventions among individuals infected and not infected with human immunodeficiency virus (HIV) in developing countries, and to assess the effectiveness of interventions targeted specifically at people living with HIV. METHODS: We conducted a systematic review and meta-analysis of papers on positive prevention behavioural interventions in developing countries published between January 1990 and December 2006. Standardized methods of searching and data abstraction were used. Pooled effect sizes were calculated using random effects models. FINDINGS: Nineteen studies met the inclusion criteria. In meta-analysis, behavioural interventions had a stronger impact on condom use among HIV-positive (HIV+) individuals (odds ratio, OR: 3.61; 95% confidence interval, CI: 2.61-4.99) than among HIV-negative individuals (OR: 1.32; 95% CI: 0.77-2.26). Interventions specifically targeting HIV+ individuals also showed a positive effect on condom use (OR: 7.84; 95% CI: 2.82-21.79), which was particularly strong among HIV-serodiscordant couples (OR: 67.38; 95% CI: 36.17-125.52). Interventions included in this review were limited both in scope (most were HIV counselling and testing interventions) and in target populations (most were conducted among heterosexual adults or HIV-serodiscordant couples). CONCLUSION: Current evidence suggests that interventions targeting people living with HIV in developing countries increase condom use, especially among HIV-serodiscordant couples. Comprehensive positive prevention interventions targeting diverse populations and covering a range of intervention modalities are needed to keep HIV+ individuals physically and mentally healthy, prevent transmission of HIV infection and increase the agency and involvement of people living with HIV.